Problematika Perempuan Menikah Penderita HIV/AIDS dalam Analisis Kuasa Tubuh Foucoult di Kota Medan - Andriansyah, Dedi; Supsiloani, Supsiloani; Febryani, Ayu; Nur Azmi, Siti Wardani; Tarigan, Lisbhet Br (Jurnal Antropologi Sumatera, 2023)
This research focuses on the problems experienced by married women suffering from HIV AIDS with a theoretical study of Michel Foucoult's body power. The design of this research is qualitative research with a phenomenological approach. This aims to reflect the life world of HIV AIDS cases among married women in the city of Medan. There are several things that underlie the permissive state of the informants which cannot be separated from the pressure (determinism) of cultural values that have been constructed into the informants' understanding. The state of determinism that influences this problem includes the cultural value of the household which provides space for the construction of patriarchal domination. This then presents the episteme of "serving" the husband which creates oppression (subaltern) in women. Not only do they face chronic health problems, but also complicated household problems due to their illness. Even though this woman's position is also that of a victim who was infected by her husband